familiar form?

Calculus Level 3

4 k = 0 ( 1 ) k 2 k + 1 = ? \large 4 \sum_{k= 0}^{\infty}\dfrac {(-1)^k}{2k+1}=?

Give your answer to 3 decimal places.


The answer is 3.141.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Mar 19, 2018

Relevant wiki: Maclaurin Series

Using Maclaurin series, we have:

k = 0 ( 1 ) k 2 k + 1 x 2 k + 1 = tan 1 x Putting x = 1 k = 0 ( 1 ) k 2 k + 1 = tan 1 1 = π 4 4 k = 0 ( 1 ) k 2 k + 1 = π 3.142 \begin{aligned} \sum_{k=0}^\infty \frac {(-1)^k}{2k+1}x^{2k+1} & = \tan^{-1} x &\small \color{#3D99F6} \text{Putting }x = 1 \\ \sum_{k=0}^\infty \frac {(-1)^k}{2k+1} & = \tan^{-1} 1 = \frac \pi 4 \\ 4 \sum_{k=0}^\infty \frac {(-1)^k}{2k+1} & = \pi \approx \boxed{3.142} \end{aligned}

Muhammad Dihya
Mar 18, 2018

this is the idea: 4 i = 0 ( 1 ) k 2 k + 1 = π 4\displaystyle \sum_{i = 0}^{\infty}\dfrac {(-1)^k}{2k+1} = \pi and π = 3.1415... \pi = 3.1415...

i get this from wolfram alpha

i'm sorry for who doesn't know this exspression

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...